THE INFLUENCE OF HUMAN RESOURCES COMPETENCIES ON WORK PRODUCTIVITY AT PT. INTIDRAGON SURYATAMA MOJOKERTO - Yulaidin, Totok (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: This research aims to examine the impact of human resource competency on work productivity within the footwear industry, which is characterized by its labor-intensive nature and the necessity for skilled employees to enhance both effectiveness and efficiency in production. Design/Methodology/Approach: The study employs a quantitative approach, gathering questionnaire data from a diverse group of respondents to assess the influence of competency on work productivity. Regression analysis is utilized to quantify the level of impact that employee competency has on productivity, allowing for a detailed exploration of this relationship. Practical Implications: The findings reveal a positive influence of employee competency on productivity enhancement, underscoring the critical importance for industries, particularly those that are labor-intensive like the footwear sector, to invest in the development of worker competencies. By doing so, these industries can improve their competitive edge and operational efficiency, leading to better overall performance and sustainability in the market.